(untitled) (Research, Society and Development, 2021)
Mato Grosso (MT) is the largest grain producer in Brazil and there are few studies dealing with soybean losses during harvest. The studies are usually specific and does not allow a general overview of what happens in the field. Therefore, the objectives of this study was: (i) accomplish a larger survey about losses, due to the harvester, characterizing the fleet and operation conditions; (ii) identify the usage of embedded technologies and (iii) identify losses associated with operational problems found in fields. The losses due to the harvester were evaluated using the template method, collecting data regarding losses due to the header and internal mechanisms for all 64 machines evaluated in the Mid-North and Northeast regions of MT throughout the 13/14 and 14/15 seasons. Use of embedded technology was accomplished using spreadsheets, as well as harvester fleet characterization. The losses due to operation problems were evaluated according to the specific problems found in the visited properties. It was found that grain moisture content was greater than 19% (considered above ideal) for more than 50% of the evaluations. However, this is an inevitable situation due to the weather conditions of MT during soybean harvesting. In terms of losses due to machine, 60% of the harvesters presented losses bellow the tolerance level (60 kg ha-1), with situations of only 20 kg ha-1 being found. It was possible to demonstrate that operational problems encountered on several occasions, have a greater impact on losses when compared to the evaluated machines, but in most cases, they are not considered.